PADA BEBERAPA TAHUN TANAM KOMPOSISI DAN KEANEKARAGAMAN JENIS NEKTON MANGROVE DI PANTAI UTARA REMBANG - , YANU A. PRATAMA, Dr. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mangrove forest is one of the ecosystems in coastal areas that has a very important role in supporting fisheries productivity, as a nursery ground (magnification place) and spawning ground for a variety of aquatic species. Nekton is one of the marine biota that its life depends on mangrove forests. The problem in this research is how the composition and diversity of nekton in recent years of planting mangroves in North Coast of Rembang. This research aims to find out the composition and diversity of nekton as the result of mangrove forest rehabilitation in Rembang. The method used was direct observation toward transek line planted in 2000, 2001, and 2005 by making a 5m x 5m plot in every 10m. Each plot was observed in term of number and type of nekton, the vegetation and the water chemistry physical factors. The data got, then were calculated to get the density and the species diversity. Vegetation composition in 2000 consisted of Rhizophora mucronata, 2001 consisted of Rhizopora mucronata, Rhizophora apiculata and Avicennia marina, while in 2005 consisted of Rhizophora mucronata. Nekton composition consisted of 2000 glodok fish, balanak fish, shrimp, mud crab, oyster, and long snail.Nekton species indeks diversity in 2000 was 1.4128, 1.1468 for 2001, and in 2005 was 1.4258. The higher planting year the greater diversity of the nekton species.